O coordenador pedagógico e os condicionantes de um trabalho bem-sucedido no cotidiano de uma escola estadual paulista - Petri, Claudia Maria Micheluci (2016)
The following research, with qualitative approach, aims to investigate and analyze which are the conditioning agents that contribute to a pedagogical coordinator from public schools of São Paulo develop a succeeded work. The subject of this survey was a pedagogical coordinator who actuates in the first years of an elementary school located in the suburb of this state.The specific objectives are to identify the knowledges that are constraints and contribute to the development of the pedagogical coordinator‟s act; recognize the external constraints that influence the pedagogical coordinator‟s behavior in her daily activities; analyze how such professional uses the knowledges in the different situations that may appear in her work and contribute to the production of insights over the pedagogical effort.To reach such objectives bibliographic studies to cover the theoretical basis; documental research based on Education Secretary of State of São Paulo legislation and analysis of registrations taken by the coordinator; observation of the school environment and interview with this professional to collect data. Paro‟s definition of constraints were used in this paper; however, some adaptations were made here. Such theoretical framework has as basis Tardif‟s teaching knowledges, considered internal constraints: the ones adopted by the pedagogical coordinator to deal with the necessities of a school routine. Institutional tasks and school types of relationships were considered the external conditioning agents. Four categories of data analysis based on theoretical framework were created: professional training, professional experience, familiarity with subject guidelines and interpersonal relationship applied to the working area. Results have revealed that professional and experiential understanding designed by this coordinator, such as the knowledge of subject guidelines constitute solid framework to the successful professional performance that she obtained, inclusive promoting a change in the teachers acting and improving the learning process of the students. Considering the external constraints, it is possible to perceive that the training offered by Diretoria de Ensino, the legislation that holds responsibility for the pedagogical coordinator‟s function, the relationship of the school community are important aspects used as baseline for that professional exercise the role of trainer of her group of teachers and transforming the school environment